BMI and Medically Certified Long‐Term Sickness Absence Among Japanese Employees. Issue 2 (23rd January 2020) - Endo, Motoki; Inoue, Yosuke; Kuwahara, Keisuke; Nishiura, Chihiro; Hori, Ai; Ogasawara, Takayuki; Yamaguchi, Miwa; Nakagawa, Tohru; Honda, Toru; Yamamoto, Shuichiro; Okazaki, Hiroko; Imai, Teppei; et al.
Abstract : Objective: In contrast to the association between excess weight and sickness absence (SA), the association in relation to underweight has been under‐researched. This study aimed to examine the effects of BMI at both extremes of its distribution on SA. Methods: Data came from the Japan Epidemiology Collaboration on Occupational Health study of 77, 760 workers aged 20 to 59 years (66, 166 males, 11, 594 females). Information was collected on medically certified long‐term SA (LTSA) (i.e., SA lasting ≥ 30 consecutive days) from April 2012 to March 2017. A sex‐specific Cox proportional hazards model was used to investigate the associations. Results: Among males, both obesity (hazard ratio [HR] = 1.81, 95% CI: 1.50‐2.17) and underweight (HR = 1.56, 95% CI: 1.23‐1.96) were significantly associated with LTSA compared with normal weight. This U‐shaped association between BMI categories and LTSA was observed both for mental and physical disorders. Among females, an elevated risk was observed among those with overweight (HR = 1.54, 95% CI: 1.16‐2.05). Conclusions: In a cohort of the Japanese working‐age population, both obesity and underweight were associated with a greater risk of LTSA in males. Future research should not overlook the excess risk of LTSA associated with underweight.